Associations between a safety prequalification survey and worker safety experiences on commercial construction sites. Issue 9 (9th June 2020) - Dennerlein, Jack T.; Weinstein, Daniel; Huynh, Whitney; Tessler, Jamie; Bigger, Lauren; Murphy, Lauren; Manjourides, Justin
Abstract: Background: While assessment of subcontractors' safety performance during project bidding processes are common in commercial construction, the validation of organizational surveys used in these processes is largely absent. Methods: As part of a larger research project called Assessment of Contractor Safety (ACES), we designed and tested through a cross‐sectional study, a 63‐item organizational survey assessing subcontractors' leading indicators of safety performance. We administered the ACES Survey to 43 subcontractors on 24 construction sites. Concurrently, we captured the safety climate of 1426 workers on these sites through worker surveys, as well as injury rates, for the duration of the project. Results: At the worksite level, higher average ACES scores were associated with higher worker safety climate scores ( P < .01) and lower rates of injury involving days away ( P < .001). Within subcontracting companies, no associations were observed between ACES and worker safety climate scores and injuries. Conclusions: These results suggest the overall and collective importance of the construction project and its worksite in mediating worker experiences, perhaps somewhat independent of the individual subcontractor level.